Given:
There are given the equation:
![\begin{gathered} x=-y-6...(1) \\ -7x+6y=-10...(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pm1ykckzm9s8tr7ayzepvgpfxo4i290i4b.png)
Step-by-step explanation:
From the equation (1):
Put the value of x into the equation (2):
So,
From the equation (2):
![\begin{gathered} \begin{equation*} -7x+6y=-10 \end{equation*} \\ -7(-y-6)+6y=-10 \\ 7y+42+6y=-10 \\ 13y=-10-42 \\ 13y=-52 \\ y=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vt3z0qpzd7gnayrx4p4znwevjvq3077tta.png)
Now,
Put the value of y into the equation (1):
So,
From the first equation:
![\begin{gathered} \begin{equation*} x=-y-6 \end{equation*} \\ x=-(-4)-6 \\ x=4-6 \\ x=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lpd7h1j05mhv1bo6qbc7atqhh6xcbtiv7k.png)
Final answer:
Hence, the ordered pair of the solution is shown below:
![(-2,-4)](https://img.qammunity.org/2023/formulas/mathematics/college/g453g15ypjjen36gxw1l06qfh7dlll5yrg.png)